2019
DOI: 10.1186/s13046-019-1373-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting metastatic breast cancer with peptide epitopes derived from autocatalytic loop of Prss14/ST14 membrane serine protease and with monoclonal antibodies

Abstract: Background In order to develop a new immunotherapeutic agent targeting metastatic breast cancers, we chose to utilize autocatalytic feature of the membrane serine protease Prss14/ST14, a specific prognosis marker for ER negative breast cancer as a target molecule. Methods The study was conducted using three mouse breast cancer models, 4 T1 and E0771 mouse breast cancer cells into their syngeneic hosts, and an MMTV-PyMT transgenic mouse strain was used. Prss14/ST14 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Typically, adjuvants are compounds that enhance the quality, potency and longevity of antigen-specific immune responses. Freund's complete adjuvant (CFA), a water-in-oil emulsion containing inactivated mycobacteria, generally appears to induce a T H 1 type immune response ( 8 9 ). In addition, Freund's incomplete adjuvant (IFA) without mycobacteria, together with CFA can induce effective T H 1 and T H 2 type immune responses ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, adjuvants are compounds that enhance the quality, potency and longevity of antigen-specific immune responses. Freund's complete adjuvant (CFA), a water-in-oil emulsion containing inactivated mycobacteria, generally appears to induce a T H 1 type immune response ( 8 9 ). In addition, Freund's incomplete adjuvant (IFA) without mycobacteria, together with CFA can induce effective T H 1 and T H 2 type immune responses ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the method by which alum modifies the immune system has not been fully understood. It is shown to induce a strong T H 2 immune response ( 9 11 ) and is also linked to serious autoimmune outcomes and adverse effects including association with breast cancer induction ( 12 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that knockdown of Prss14/epithin reduces cell migration (9,10) and metastatic ability of breast cancer cells such as 4T1 (9) and EO771 (11). When a specific monoclonal antibody raised against the activation loop portion of Prss14/epithin was injected into a PyMT breast cancer mouse model, metastasis was significantly reduced (11).…”
mentioning
confidence: 99%